UO‘K 677.024.544 Theoretical Analysis of the Coefficient of Friction Induced by the Pressure Force of a Vertical Rope Acting from Above and Below - Homidov, Qahramon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article presents a theoretical study of the coefficients of friction between a rope and a vertical pole when pressure forces are applied from above and below. To facilitate understanding of the mechanical processes, illustrations are provided. A mathematical relationship is established between the angle of the rope's winding around the pole and the work done by the frictional force. In developing this relationship, a small surface area is selected, and the characteristics of the forces acting on that area are examined. The results obtained are applied to the entire surface. Utilizing the solution of the established equation, a function relating the work of the frictional force to time is formulated, and its graph is presented. The plotted graphs fully represent the processes in practice, thereby confirming the theoretical and mechanical accuracy of the studied object.